Gradient Nanostructure: A Flexible Strategy to Fabricate Gradient Plasmonic Nanostructures (Adv. Mater. Interfaces 24/2018). Issue 24 (20th December 2018) - Ai, Bin; Larson, Steven; Bradley, Layne; Zhao, Yiping
Abstract : In article number1800975 Bin Ai, Yiping Zhao, and coworkers present a fabrication strategy to produce gradient plasmonic nanostructures by a physical vapor deposition on a curved mask substrate covered with a monolayer of close‐packed nanospheres. A plasmonic library is easily established in a single fabrication. The strategy can in principle produce a wide range of gradient nanostructures and further be used for flexible components in optical devices.